Acute Effects of Intermittent and Continuous Static Stretching on Hip Flexion Angle in Athletes with Varying Flexibility Training Background - Olyvia Donti; Vasiliki Gaspari; Kostantina Papia; Ioli Panidi; Anastasia Donti; Gregory C. Bogdanis (MDPI AG, 2020)
Τhis study examined changes in hip joint flexion angle after an intermittent or a continuous static stretching protocol of equal total duration. Twenty-seven female subjects aged 19.9 ± 3.0 years (14 artistic and rhythmic gymnasts and 13 team sports athletes), performed 3 min of intermittent (6 × 30 s with 30 s rest) or continuous static stretching (3 min) of the hip extensors, with an intensity of 80−90 on a 100-point visual analogue scale. The order of stretching was randomized and counterbalanced, and each subject performed both conditions. Hip flexion angle was measured with the straight leg raise test for both legs after warm-up and immediately after stretching. Both stretching types equally increased hip flexion angle by ~6% (continuous: 140.9° ± 20.4° to 148.6° ± 18.8°, p = 0.047; intermittent: 141.8° ± 20.3° to 150.0° ± 18.8°, p = 0.029) in artistic and rhythmic gymnasts. In contrast, in team sports athletes, only intermittent stretching increased hip flexion angle by 13% (from 91.0° ± 7.2° to 102.4° ± 14.5°, p = 0.001), while continuous stretching did not affect hip angle (from 92.4° ± 6.9° vs. 93.1° ± 9.2°, p = 0.99). The different effect of intermittent vs. continuous stretching on hip flexion between gymnasts and team sports athletes suggests that responses to static stretching are dependent on stretching mode and participants training experience.